2014
DOI: 10.1590/s0102-8650201400140012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygen therapy as hepatic preconditioning in rats submitted to hepatic ischemia/reperfusion injury

Abstract: PURPOSE:To analyze the role of hyperbaric oxygen therapy as hepatic preconditioning in rats submitted to hepatic ischemia and reperfusion. METHODS:Wistar rats were randomly divided into three groups: SHAM, rats submitted to surgical stress without hepatic ischemia and reperfusion, I/R, rats submitted to total hepatic pedicle ischemia for 30 min, followed by 5 min of reperfusion; HBOI/R, rats submitted to 60 minutes of hyperbaric oxygen therapy at 2 atm and immediately submitted to the experimental protocol of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…Thus, the quantification of lipoperoxides in these tissues may indicate the degree of oxidative stress imposed by I/R. In this regard, previous animal studies have shown that livers submitted to I/R present elevation of MDA, a final product of lipoperoxidation 27,28 . The tissue MDA, which indicates the degree of oxidative stress, increased in the I/R group, but this increment was not statistically significant.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Thus, the quantification of lipoperoxides in these tissues may indicate the degree of oxidative stress imposed by I/R. In this regard, previous animal studies have shown that livers submitted to I/R present elevation of MDA, a final product of lipoperoxidation 27,28 . The tissue MDA, which indicates the degree of oxidative stress, increased in the I/R group, but this increment was not statistically significant.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Intriguingly, Losada et al . have reported that HBO pre‐conditioning protects the liver from mitochondrial dysfunction and decreases the levels of hepatic injury markers during the ischaemia and reperfusion processes. Although HBO pre‐conditioning has been proven to effectively eliminate ALT and to improve the expression of HO‐1, it cannot decrease the levels of aspartate aminotransferase (AST) and malondialdehyde (MDA) .…”
Section: Pre‐treatments With Un‐physiological Oxygen Content Before Hmentioning
confidence: 99%
“…The protective effect of GCDCA has not been described before, but it is known that cells can adapt to cellular stress and thereby gain resistance to cytotoxic challenges. Previous studies have shown that ischemic preconditioning [ 25 ], preconditioning with hyperbaric hepatic hyperoxia [ 26 ], glutathione [ 27 ], or helium [ 28 ] is protective against ischemia/reperfusion injury after liver transplantation. Adaptation to cellular stress by preconditioning as observed in this study can be defined by the principles of hormesis.…”
Section: Discussionmentioning
confidence: 99%